THE SCHOLARS OF EGYPT AND SHAMTHAT THEIR MENTIONING STATED IN THE BOOK OF (NABAHAT AL-BALLAD AL-KHAMIL WITH THOSE WHO VISITED IT OF AL-'AMATHIL) FOR THE HISTORIAN AL-ARBALI (DIED 637 H. ) - Dr. Abeer Enayat Saeed Dosaki (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Al-Arbali is a prominent historical and literary character that left its knowledge stamps through several books amongst what he allocated to highlight the aspects of comprehensive development and care for all facilities that the historical City of Arbal had witnessed (his city and home town) at the era of its most prominent Muslim rulers and the civilized and scientific place it reached and their role in transforming the country into an eminent destination of knowledge in the field of learning and teaching and a stations for his senior scholars.